2019
DOI: 10.1038/s41598-019-41621-3
|View full text |Cite
|
Sign up to set email alerts
|

CCL21/CCR7 axis regulating juvenile cartilage repair can enhance cartilage healing in adults

Abstract: Juvenile tissue healing is capable of extensive scarless healing that is distinct from the scar-forming process of the adult healing response. Although many growth factors can be found in the juvenile healing process, the molecular mechanisms of juvenile tissue healing are poorly understood. Here we show that juvenile mice deficient in the chemokine receptor CCR7 exhibit diminished large-scale healing potential, whereas CCR7-depleted adult mice undergo normal scar-forming healing similar to wild type mice. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…Recent studies by Joutoku et al [ 24 ], using a different animal model showed that local administration of CCL21 to adult rabbits at the knee joints can enhance cartilage repair post osteochondral defect. In Joutoku et al [ 24 ] studies, the experimental defect affected both articular cartilage and osteochondral bone and was deep enough to reach bone marrow [ 24 ]. This allowed the infiltration of mesenchymal stem cells from bone marrow to the injured knee joints for cartilage regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies by Joutoku et al [ 24 ], using a different animal model showed that local administration of CCL21 to adult rabbits at the knee joints can enhance cartilage repair post osteochondral defect. In Joutoku et al [ 24 ] studies, the experimental defect affected both articular cartilage and osteochondral bone and was deep enough to reach bone marrow [ 24 ]. This allowed the infiltration of mesenchymal stem cells from bone marrow to the injured knee joints for cartilage regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, juvenile mice deficient in CCR7 displayed significantly impaired cartilage healing postinjury (longitudinal full-thickness cartilage injury in the trochlear groove) compared to wild-type controls, while adult CCR7-deficient mice developed similar fibrocartilaginous tissue as controls in response to injury. Moreover, exogenous delivery of CCL21 ligand, whose transient expression had been identified at the injury site in juvenile mice, led to enhanced healing in adult rabbit after osteochondral defects [18]. Collectively, these findings suggest that this signaling pathway could be a promising target for the enhancement of adult tissue regeneration.…”
Section: Aging and The Regenerative Potentialmentioning
confidence: 78%
“…Yet, the biological and molecular mechanisms responsible for enhanced regenerative competence at a younger age remains poorly understood. Joutoku et al have recently studied the involvement of chemokines, namely the CCL21/CCR7 axis, in regulating cartilage regeneration at a younger age [18]. Interestingly, juvenile mice deficient in CCR7 displayed significantly impaired cartilage healing postinjury (longitudinal full-thickness cartilage injury in the trochlear groove) compared to wild-type controls, while adult CCR7-deficient mice developed similar fibrocartilaginous tissue as controls in response to injury.…”
Section: Aging and The Regenerative Potentialmentioning
confidence: 99%
See 2 more Smart Citations